Transformasi Praktik Ritual pada Upacara Manusa Yadnya di Bali - Wahyuni, Anak Agung Ayu Rai; Sunaryo, Fransiska Dewi Setiowati; Sidemen, Ida Ayu Wirasmini (Humanis; Vol 29 No 2 (2025), 2025)
This research aims to reveal the transformation of religious ritual practices at the Manusa Yadnya ceremony in Bali. The Manusa Yadnya ceremony is interesting to discuss because it has transformed from traditional to modern due to the influence of modernization. This article discusses the form of transformation of religious ritual practices in the Manusa Yadnya ceremony. These factors influence the transformation and the challenges faced by the venue of the Manusa Yadnya ceremony which is carried out in the griya and the event organiser.  The research questions were answered with qualitative research methods. Research data was collected through observation, interviews, and literature study. The theory used is modernization theory. The results showed that the change in religious ritual practices was due to the Balinese desire for efficiency and practicality in the implementation of Manusa Yadnya ritual practices without reducing the meaning contained in it.